2020
DOI: 10.1002/ams2.608
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frailty on protocol‐based weaning from mechanical ventilation in patients with sepsis: a retrospective cohort study

Abstract: Aim: Frailty has been shown to be associated with prolonged mechanical ventilation (MV). However, due to limited physiological data, it has been unclear how frailty affects weaning from MV in septic patients subjected to a specific weaning protocol. Methods: This was a single-center retrospective cohort study. The study included patients with sepsis on MV who underwent protocol-based weaning between August 2015 and December 2018. Frailty was defined as a Clinical Frailty Scale score 4 or more. The association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Many patients with sepsis are at risk of severe loss of muscle mass and quality ( 16 , 34 ). Patients who become frail after sepsis may have an increased risk of extubation failure, may more frequently require a tracheostomy, and may have difficulties weaning from a ventilator ( 35 , 36 ). Obesity can prevent muscle wasting and weakness in sepsis and demonstrates a different metabolic response to sepsis in comparison with lean patients by preserving muscle mass while losing fat mass ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with sepsis are at risk of severe loss of muscle mass and quality ( 16 , 34 ). Patients who become frail after sepsis may have an increased risk of extubation failure, may more frequently require a tracheostomy, and may have difficulties weaning from a ventilator ( 35 , 36 ). Obesity can prevent muscle wasting and weakness in sepsis and demonstrates a different metabolic response to sepsis in comparison with lean patients by preserving muscle mass while losing fat mass ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preexisting clinical frailty is associated with worse outcomes, including increased mortality for elderly sepsis patients [ 382 ], and frailty together with age and disease severity are identified as predictors of long-term mortality in very old intensive care patients with sepsis [ 383 ]. Finally, a longer duration of mechanical ventilation in frail sepsis patients who underwent protocol-based weaning was also observed [ 384 ].…”
Section: Neutrophil Migration In Certain Groups Of Patients With An I...mentioning
confidence: 99%
“…We believe that the presence or absence of DNI orders should therefore be carefully adjusted for, so that frail patients do not receive inadequate treatment based on overly pessimistic predicted outcomes. In this regard, we recently reported that frailty was associated with delay in ventilator weaning in patients with sepsis (4). Given that our frail patients frequently presented with respiratory failure, we speculate that they were more ventilator-dependent due not only to limitations placed on their treatment but also to respiratory muscle weakness and atrophy.…”
Section: To the Editormentioning
confidence: 99%